An Overview of the Production Potentials of Gas in Tight Sands and Shale Gas Formations Worldwide: A Key Factor for Consideration in Nigeria - Oyindobra Ossai, Patrick Godwin; Ohia, Princewill Nnaemeka; Izuwa, Nkemakolam Chinedu (Journal of Advanced Research in Petroleum Technology & Management; Vol 4 No 3&4 (2018): Journal of Advanced Research in Petroleum Technology & Management, 2021)
As at today, Nigeria is supposed to be well positioned to generate about 40000 MW of power on a daily basis for at least 68 years from the Country’s indigenous gas reserves that is estimated at 181 Tcf. This enormous gas reserve makes Nigeria the largest gas superpower in Africa and the ninth largest in the world. Despite her massive gas resources, Nigeria generates only about 4000 KW of power from gas utilization in full operation from its gas-powered turbine plants. This is not up to one-tenth of the abundance of its existing gas resources. Power generation and supply today in Nigeria is still very epileptic due to shortage of gas supply to its gas-powered turbine plants. As an overview, this research work focused on the enormous potentials and production capabilities of gas produced from tight gas sands and shale gas formations in the United States (Case 1) and outside the United States (Case 2). Our research work also looked at gas production from tight gas sands/shale gas formations and their respective potentials that are relevant to the economic growth of any nation (as in case 1 and 2 respectively). The intent of this study is to spur relevant stakeholders in Nigeria and other African countries to critically start looking at how best to harness the potentials of gas production from tight gas sands and shale gas formations. This can without doubt boost their nation’s economy on commercial basis globally.